Factors Influencing Anxiety among Patients in a Dental Setting: A Cross-sectional Study - Shanthi Vanka; Samar Hesham Almwailighi; Lujain Jamil Sharqawi; Ohoud Zaki Alaidaroos; Diala Tariq Ashour; Heba Manar Barakat; Othman Wali; Amit Vanka (Journal of Clinical and Diagnostic Research)
Introduction: Dental Anxiety (DA) is a well-known obstacle that influences how patients behave and feel about receiving dental care. The Modified Dental Anxiety Scale (MDAS) is a widely used instrument for evaluating DA in patients attending dental clinics. Aim: To determine the variables affecting DA in patients at a private dentistry college in Jeddah. Materials and Methods: A cross-sectional study was conducted at Department of Preventive Dental Sciences, Ibn Sina National College for Medical Studies, Jeddah, Makkah, Saudi Arabia, from December 2023 to March 2024. A self-reported questionnaire was used as the data collection tool. The study comprised a total of 346 participants, with responses collected electronically via Google Docs. Participants were categorised into three groups—low, moderate and high DA—based on established risk indicators. The analysis of responses employed descriptive statistics, presented as mean±standard deviation. Associations between variables were assessed using the Chi-square test, with a p-value of less than 0.05 considered statistically significant. Results: Among participants aged 18 to 30 years, 73 individuals (54.1%) reported low anxiety levels, 56 individuals (41.5%) reported moderate anxiety and 6 individuals (4.4%) reported high anxiety levels. In the cohort of participants older than 30 years, 84 individuals (39.8%) exhibited low anxiety, 103 individuals (48.8%) exhibited moderate anxiety and 24 individuals (11.4%) exhibited high anxiety levels. Examining gender differences, 58 males (58%) reported low levels of anxiety, while 8 males (8%) reported high levels. Comparatively, 99 females (40.2%) reported low anxiety and 22 females (8.9%) reported high anxiety levels. Although a majority of participants indicated low levels of anxiety, among postgraduate individuals, 6 (26.1%) reported high anxiety levels. Participants were also queried regarding their prior dental visits and of those who responded affirmatively, 157 individuals (45.4%) reported low anxiety, 159 individuals (45.9%) reported moderate anxiety and 30 individuals (8.6%) reported high anxiety. Conclusion: The findings of the present study indicate that DA is significantly influenced by various factors, including age, gender, occupation, self-perceived oral healthcare and prior dental visit experiences. Addressing these variables may enhance the effectiveness of strategies aimed at mitigating DA among patients visiting dental clinics.